Competition and bank efficiency in Peru through the Boone index - Jiménez Rivera, William Miguel (2020)
In the present work the level of competition and banking efficiency in Peru is studied for the period 2011 2016 with monthly frequency data, through the estimation by the panel data technique of the Boone index for the banking credit system in global and disaggregated into four types of loans, such as wholesalers, retailers, consumer and mortgage. Given the importance of an efficient and competitive banking system for the development of countries, this study shows evidence of the evolution of the Boone Index, one of the indicators most used by the new empirical industrial organization to measure competition and efficiency in industries. Specifically, evidence is left on the hypothesis that concentration increases competition and thus efficiency, does not show clear results at all. JEL: G21; L11.